Results of treatment of children with refractory anaemia with excess blasts (RAEB) and RAEB in transformation (RAEBt) in Great Britain 1990-99. - Webb, D; Passmore, S; Hann, I; Harrison, G; Wheatley, K; Chessells, J (2002)
Between 1990 and 1999, 36 children with refractory anaemia with excess blasts (RAEB) and RAEB in transformation (RAEBt), not associated with Down's syndrome, were diagnosed in Britain. A total of 31 children received intensive chemotherapy, six of whom proceeded to a bone marrow allograft in first remission, whereas two received an autograft. Of the 23 given chemotherapy only, four died of toxicity, 10 relapsed and nine are alive in first remission. Out of the 10 who relapsed, four are alive and disease-free following an allograft. Out of the 6 children given an allograft in first remission, two died of disease and four are alive in first remission. Both children given an autograft died of disease. Two children received an allograft without prior chemotherapy but died of toxicity. Three children received supportive care only, and one child survived. The overall survival was 51% at 5 years, and was superior in children with RAEBt (63%) compared with RAEB (28%, P = 0.03). Cytogenetics were available in 35 cases. Monosomy 7 was the most common abnormality (33% of cases). Survival in children with monosomy 7 was 22% at 5 years compared with 66% for the other patients (P = 0.05). Allowing for cytogenetics, outcomes of therapy appear similar to those for de novo acute myeloid leukaemia (AML), and it is appropriate for children with RAEB/RAEBt to be registered in AML trials.